ANALISIS STRATEGI PEMBELAJARAN UNTUK MENGATASI KESULITAN BELAJAR MATEMATIKA SISWA KELAS IV SD - Dimas Ilham Prayoga; Waridah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze learning strategies for addressing difficulties in learning mathematics, particularly in solving word problems, among fourth-grade elementary school students. The main problem identified in the field is the students’ low problem-solving skills and mathematical literacy resulting from monotonous conventional (lecture-based) teaching methods and the minimal use of learning media. The research design employed was qualitative research conducted at SDN 05 Nanga Nuak with a sample of 25 students. Data were collected through observation, interviews, and documentation, and were subsequently analyzed through the stages of data reduction, data presentation, and drawing conclusions.